Isolation, identification and optimization of a new extracellular lipase producing strain of rhizopus sp. - Kantak, Jayshree B.; Bagade, Aditi V.; Mahajan, Siddharth A.; Pawar, Shrikant P.; Shouche, Yogesh S.; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2011)
A lipolytic mesophilic fungus which produces lipase extracellularly was isolated from soil. Based on ITS1-5.8S-ITS4 region sequences of ribosomal RNA, it was concluded that the isolate JK-1 belongs to genus Rhizopus and clades with Rhizopus oryzae. The present paper reports the screening, isolation, identification, and optimization of fermentation conditions for the production of lipase (EC 3.1.1.3). Culture conditions were optimized, and the highest lipase production was observed in basal medium with corn steep liquor as nitrogen source and glucose as carbon source. Maximum lipase production was observed at 72 h, which is about 870 U/ml. Optimization of fermentation conditions resulted in 16-fold enhancement in enzyme production.
Keywords: Corn steep liquor; Fermentation; ITS region; Lipase; Medium optimization; Rhizopus